Advantages and Disadvantages of the Direct Method in Teaching English (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The Direct Method (DM) is a language teaching approach emphasizing immersion in the target language, where students learn exclusively through the target language without relying on translation or explicit grammar instruction. This method has been widely used to improve speaking and listening skills by promoting spontaneous communication. Theoretical foundations, such as Krashen's Input Hypothesis and Vygotsky's socio-cultural theory, support the method’s focus on contextual and interactive learning. While the effectiveness of DM in enhancing oral fluency is well-documented, its impact on literacy skills, particularly writing and grammar accuracy, remains underexplored. This study aims to address the knowledge gap by analyzing the strengths and limitations of the Direct Method, particularly its effect on speaking, listening, and writing proficiency. Findings reveal that DM significantly improves oral fluency and listening comprehension but shows limitations in grammar acquisition and writing skills. This research contributes new insights into how DM can be complemented with other instructional strategies to address its weaknesses, offering a more balanced approach to language acquisition. The study suggests that while DM is effective for spoken communication, integrating explicit grammar instruction and writing practice is crucial for comprehensive language proficiency.